Developing Android-based Disabled Data Information System to List Students with Disabilities (SIDABEL) - Imam Yuwono; Dewi Ekasari Kusumastuti; Mohd Hanafi Mohd Yasin; Andy Azhari; Asmariah Asmariah; Purnamasari Purnamasari (STAI Hubbulwathan Duri, 2024)
Manually registering the disabled population in riverbank areas is time-consuming and error-prone. This research aimed to develop an Android-based application for efficient and effective data collection of the disabled population. Using the ADDIE design within the Research and Development (RD) framework, participants included six teachers from Paramita Graha B/C Special School, ten teachers from Public Special School 3 Banjarmasin, twelve teachers from Harapan Bunda Special School, and ten Banua Anyar sub-district officers. Data collection involved interviews, questionnaires, and documentation, analyzed through both quantitative and qualitative methods. The study identified the needs of teachers and sub-district officers, guiding the development of the Disabled Data Information System (SIDABEL) application. The application’s feasibility was validated with average scores of 3.71 from material experts and 3.63 from media experts, indicating it was appropriate with revisions. Teacher assessments rated the application 3.81, 3.94, and 3.63 from Paramita Graha, Public Special School 3 Banjarmasin, and Harapan Bunda, respectively, categorizing it as good with some suggestions for improvement. After revisions, sub-district officers tested the application, resulting in a final score of 4.55 in the very good category. The SIDABEL application addresses inefficiencies and errors in manual data collection, leading to high user satisfaction and effectiveness in its final iteration. Further research should explore broader implementations and continuous improvements. The Android-based SIDABEL application significantly enhances the efficiency and accuracy of data collection for the disabled population in riverbank areas.